Natural Material Media as A Means of Developing A Naturalist Intelligence at Labiba Maulida Boyolali Kindergarten - Kinasih, K; Widyasari, Choiriyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aims to comprehend children's fine motor skills and their utilization of natural materials and recycled items at Labiba Maulida Kindergarten, situated in the Banyudono District of the Boyolali Administrative Region. Methodology: Qualitative methods constituted the framework for this investigation. The research focused on children in Group A at Labiba Maulida Boyolali Kindergarten. Data gathering encompassed planning, execution, and evaluation stages, with lesson planning incorporating natural materials within the school environment. Results: The learning process commenced with the delineation of annual and semester programs, weekly learning schedules, and lesson plans, alongside ongoing learning assessments utilizing anecdotal observations and checklists conducted daily and compiled on a weekly and monthly basis. This study capitalized on the availability of natural materials within the surroundings to gauge the development of naturalistic intelligence. While the ability to select appropriate natural materials is fundamental, proficiency in utilizing them for learning purposes is equally crucial. Nevertheless, challenges were encountered; certain students initially struggled to identify suitable natural materials, perceiving them as lacking educational value. Conversely, some students demonstrated an aptitude for sourcing and utilizing natural materials in their work. Teachers provided incremental support and guidance for those yet to acquire this skill, encouraging them to explore the school environment to familiarize themselves with the natural materials incorporated into the learning process. In summary, cultivating naturalistic intelligence through integrating natural materials at Labiba Maulida Kindergarten yielded demonstrable success.